2017
DOI: 10.12968/ijpn.2017.23.4.174
|View full text |Cite
|
Sign up to set email alerts
|

Does respite care address the needs of palliative care service users and carers? Their perspectives and experiences

Abstract: A reframing of respite care as an empathic response within a new palliative care approach is proposed. Within this, the centrality of the relationship is reinforced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Hindrance to carers' adoption of SC stemmed from formal providers' flawed assumption that SC will be provided for by relational support-a point also raised by Wolkowski et al(2017). This study found carers/carees often fell into a vicious circle as the care journey advanced, with diminishing relational support exacerbating isolation, while increasing caregiving responsibilities eroded time available for carers to access communities.…”
Section: Discussionmentioning
confidence: 87%
“…Hindrance to carers' adoption of SC stemmed from formal providers' flawed assumption that SC will be provided for by relational support-a point also raised by Wolkowski et al(2017). This study found carers/carees often fell into a vicious circle as the care journey advanced, with diminishing relational support exacerbating isolation, while increasing caregiving responsibilities eroded time available for carers to access communities.…”
Section: Discussionmentioning
confidence: 87%
“…It is critical for institutional decision-makers and program staff to prioritize the trust and unique care needs of families with ALS. This can be supported by maintaining consistency in staff members, upholding clear communication between staff and care partners, and building a collaborative care partnership that acknowledges the centrality of families and their care preferences [ 29 , 30 ]. Prioritizing engagement with the ALS community in the design, delivery, and evaluation may help respite care better meet the needs of families and improve service uptake.…”
Section: Discussionmentioning
confidence: 99%
“…This requires the use of judgement about the patient and their stage of illness—and again, relies on nurses to instigate referral to health psychologists and similar professionals. In addition, COPD nurses should assess the opportunities they have to refer patients to respite care, rehabilitation care and other forms of community‐based care when planning a patient's discharge—interventions that have been advocated as important elements of COPD care in other studies (Hasson et al., ; Wolkowski & Carr, ).…”
Section: Discussionmentioning
confidence: 99%
“…This study also highlights the importance of good care planning and positive interventions in COPD. Wolkowski and Carr () discuss the potential use of respite care for COPD patients that can both alleviate patient anxieties about not being able to cope at home and also give relatives a break from caring. This is certainly one intervention nurses could consider following an acute exacerbation of COPD and has been found valuable in other COPD studies (Wilson et al., ).…”
Section: Discussionmentioning
confidence: 99%